392 Agricultural Activities and Lung Cancer Mortality in France: A Nested Case-Control Analysis from the Agrican Cohort. (11th October 2013) - Tual,; B Clin,; Levêque-Morlais,; Baldi,; Lebailly,
Abstract : Objectives: Farmers have lower lung cancer rates than the general population, due to low smoking rates. Exposure to endotoxins may also play a role. These exposures do not however preclude the role of lung carcinogen exposures in farming activities. We assessed the associations between farming activities and lung cancer from a case-control analysis nested in the French agricultural cohort AGRICAN (n = 180, 060). Methods: Incident lung cancer deaths from enrolment (2005–2007) to 31/12/2009 (n = 399) were individually matched with 4 controls by year of birth and sex by incidence density sampling method. Associations between self-reported lifetime farming activities and lung cancer were estimated using conditional logistic regression, controlling for cigarettes pack years. Results: Lifetime exposure to animals was significantly related to a decreased lung cancer risk (OR = 0.59, 95% CI:0.41–0.84) with a similar association among non-smokers (OR = 0.57, 95%CI: 0.29–1.12). Non-significant decreased risks were observed for some animals: cattle, sheep/goat and horse (OR = 0.63–0.74, p = 0.10–0.15). Animal care on sheep/goat was the only task significantly inversely related to lung cancer (OR = 0.48, 95%CI: 0.25–0.94). A non-significant increased risk was associated with lifetime exposure to vineyards (OR = 1.29, 95%CI: 0.90–1.86, p = 0.17), association strengthened among non-smokers (OR = 1.84, 95%CI:0.99–3.44). An increased risk was observed for cellar work in vineyards (OR = 1.59, 95%CI:0.96–2.63, p = 0.07), strengthened and significant in non-smokers (OR = 4.06, 95%CI: 1.59–10.37). Conclusion: These findings support the role of a decreased lung cancer risk associated with animal-related exposures and suggest the role of hazardous exposures in vineyard, particularly for cellar work. The role of other potential hazardous exposures (including arsenic pesticides that have been used in France in vineyard until 2001 and in some fruit growing and potato production until mid 1970s) will be further investigated in this study using a crop-exposure matrix. Further efforts are needed to identify etiologic protective agents and hazardous exposures for lung cancer in farming.